Virilization and feminization in an adolescent boy with 45X/46XY DSD due to bilateral gonadoblastomas: A case report - Thabitha J. Hoole; Shamaali Gunawardana; Sureshi Nandani Tennekoon; Malik Samarasinghe; Sumudu Nimali Seneviratne (Elsevier, 2024)
Introduction: Children with 45X/46XY difference/disorder of sex development (DSD) have varying internal/external genitalia/gonads, Turner-like features, and increased risk of gonadal malignancy. We present a case of concomitant virilization and feminization as a unique feature of gonadoblastoma in a boy with 45X/46XY DSD. Case presentation: The patient was born with ambiguous genitalia (phallus of 2cm, perineal urethra) and a Turner-like phenotype. Ultrasound scan revealed horseshoe kidneys, intra-abdominal gonads, and Mullerian remnants. His karyotype was 45X/46XY with atypical Y chromosome. Initial gonadotrophin levels were very high. Biopsy of the bilateral gonads revealed testicular tissue. It was decided to raise the baby as a boy. Staged orchidopexy and hypospadias repair were done between 4 and 6 years of age. He remained under close clinical, biochemical and radiological follow-up for the potential development of gonadal malignancies. He developed penile enlargement at the age of11 years. Within a few months, he developed bilateral gynecomastia and rapid cystic enlargement of the gonads. Hormone quantification revealed elevated serum estrogen, a peri-pubertal testosterone level, and normal tumor marker levels. After a multidisciplinary team discussion, he underwent surgical exploration and removal of a bulky uterus and both gonads. Histology showed evidence of gonadoblastoma within the testicular and the ovarian stroma. Conclusion: Children with DSD are at high risk for developing gonadoblastomas, which can present as rapid concurrent isosexual and heterosexual pubertal development. It is critical that patients with DSD remain under close oncologic surveillance.